Premenstrual Dysphoric Disorder: Epidemiology and Treatment - Hantsoo, Liisa (Curr Psychiatry Rep, 2015)
Recently designated as a disorder in the DSM-5, premenstrual dysphoric disorder (PMDD) presents an array of avenues for further research. PMDD's profile, characterized by cognitive–affective symptoms during the premenstruum, is unique from that of other affective disorders in its symptoms and cyclicity. Neurosteroids may be a key contributor to PMDD's clinical presentation and etiology, and represent a potential avenue for drug development. This review will present recent literature on potential contributors to PMDD's pathophysiology, including neurosteroids and stress, and explore potential treatment targets.